Analysis of Parents’ Level of Trust in School Financial Transparency - Wita Wahyu Mardiningrum; Juharyanto Juharyanto; Aan Fardani Ubaidillah (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: The era of globalisation has changed various aspects of human life, including education, which is the main foundation of human resource development in Indonesia. In an effort to improve and equalise education, the government has designed education policies, as stipulated in the 1945 Constitution and Government Regulation No 47/2008 on the 12-year compulsory education programme. The implementation of this policy in Pasuruan City since 2012 involves the management of funds from the government through the BOS programme, BPOPP, and parent participation funds, which are contained in various regulations. However, the management of these funds is often a polemic in the community, especially regarding school financial transparency. This study aims to analyse the effect of financial transparency on the level of parental trust. Using the Systematic Literature Review (SLR) method. The study found that financial transparency significantly contributes to the level of parental trust and school productivity. While parental participation is important, the research shows that it does not always have a significant effect on the accountability and effectiveness of fund management. The findings emphasise the need for improvements in transparency and management of education funds to increase stakeholder trust and support sustainable development. Recommendations for improving school fund management are expected to contribute positively to the quality of education. Keywords: parents' level of trust; school financial transparency